On the delamination of a viscoelastic composite circular plate - Akbarov, SD; Rzayev, OG (CONSULTANTS BUREAU, 2003)
Delamination of a symmetric circular plate made of viscoelastic composite is studied. It is assumed that the plate has a penny-shaped crack whose edges have a minor axisymmetric imperfection. The lateral surface of the plate is clamped and is compressed by uniform radial normal forces through a rigid body. The studies are made using the exact geometrically nonlinear equations of the theory of viscoelasticity. The delamination criterion is assumed unrestrained growth of the initial imperfection. The Laplace transform and FEM are employed. In particular cases, the results are compared with those for elastic composites.
Keywords: delamination; viscoelastic composite; plate; penny-shaped crack; numerical analysis; INTERFACE CRACKS; STABILITY; BODIES; ROOTS; Mechanics